ANALISIS INTERAKSI EDUKATIF DAN INTERAKSI SOSIAL PADA PEMBELAJARAN IPS DI MTs. NURUL ULUM MALANG - Wafiyatu Maslahah; Lailatul Rofiah; Rosyidatur Rohmah M.P (Jurnal Ilmiah Hospitality, 2023)
Social studies learning in realizing the profile of Pancasila students who have noble character is reflected in good educational interactions and social interactions. The purpose of this research activity is to find out the process and impact of educative interaction and social interaction on learning in MTs. Nurul Ulum Malang. The focus of research interest this time is 1) there are only a few students who are late to class 2) students at the school do not hesitate to ask their teachers if there is something they don't understand 3) students can be open to their teachers without losing respect for their teachers 4) students at This school is a boarding school student which has embedded Islamic values ​​within itself. The method used in this research is qualitative with the type of phenomenological research. Data collection through observation, in-depth interviews and documentation. The results of this study indicate that educative interaction and social interaction in social studies learning at MTs. Nurul Ulum has been going well. Communication between teachers and students is going well. Students are more open to their teachers. So that the learning process goes well and optimally